Severe Metabolic Alkalosis and Thyroid Storm Mimicking Eclampsia in Pregnancy: A Case Report - Diego Rafi Putra Uta; Dela Putri Pratikno; Hammam Arif Shabri; Muhammad Isra Rafidin Rayyan; Safinaz Safinaz; Achmad Wahib Wahju Winarso (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Seizures during pregnancy are most attributed to eclampsia, a significant cause of maternal mortality. However, other severe conditions, such as metabolic and endocrine disorders, can present similar clinical features, creating diagnostic dilemmas. Among these, thyroid storm and severe metabolic alkalosis are rare but critical differential diagnoses that demand accurate identification to prevent inappropriate treatment and adverse outcomes. To our knowledge, few reports have described the simultaneous occurrence of thyroid storm and severe metabolic alkalosis presenting as eclampsia and successfully managed without pregnancy termination. Objective: This case report aims to present a challenging case of pregnancy-related seizures, highlighting the diagnostic difficulties that arise when severe metabolic alkalosis and thyroid storm mimic the clinical manifestations of eclampsia. Case Report: A 27-year-old woman at 27 weeks of gestation, with a history of untreated hyperthyroidism, presented with recurrent tonic-clonic seizures. The diagnosis of thyroid storm was established using the Burch-Wartofsky Point Scale (BWPS score = 60). While eclampsia was initially suspected due to severe hypertension, the absence of proteinuria prompted further investigation. Laboratory tests revealed severe metabolic alkalosis secondary to persistent vomiting, along with profound hypokalemia and hypomagnesemia, which were identified as contributors to the seizure activity. A multidisciplinary team initially considered pregnancy termination but opted for aggressive metabolic stabilization in the ICU. The patient was managed with intensive electrolyte correction, antihypertensives, and antithyroid medications. This approach led to significant clinical improvement and the stabilization of her metabolic state. Consequently, the pregnancy was preserved, and the patient was discharged in stable condition without further complications. Conclusion: This case suggests that aggressive metabolic stabilization may allow pregnancy preservation in selected patients who present with seizures due to concurrent thyroid storm and severe metabolic alkalosis. This approach can successfully prevent the unnecessary termination of pregnancy, leading to favorable outcomes for both the mother and fetus. It underscores the importance of considering a broad differential diagnosis in pregnant patients with seizures.